A Study to Determine the Effect of Egg Albumin Dressing on Peristomal Wound Healing of the Colostomy Patients in a Selected Hospital, Kolkata, West Bengal (Global Journal of Medical Research, 2021)
The researcher conducted a quasi experimental study to evaluate the effect of egg albumin dressing on peristomal wound healing in a selected hospital, Kolkata, with the objectives to assess the peristomal skin condition of colostomy patients before treatment, to evaluate the effect of egg albumin dressing on healing of peristomal area and reduction of pain, to find out the association between the peristomal wound healing and selected variables. The final study was conducted at Curzon ward, Victoria ward of SSKM hospital, Kolkata. Ethical permission was sought out from Ethical Committee of SSKM hospital, Kolkata. Informed consent was taken from all respondents. The sample was selected according to their selected criteria. The sample selection was done by purposive sampling. They were randomly assigned into two groups (experimental and control group) in 1:1 ratio. The study concluded with its limitations, implications and recommendations for conducting a study may be conducted for a longer duration of observation with the treatment.
Keywords: albumin dressing; peristomal wound healing; colostomy patients; egg albumin